(untitled) (Annals of Medical Research, 2021)
Aim: This study aims to determinate Quality of life, from the perspective of nurses and Afghan Migrant children in Turkey. Material and Methods: This study used method includes quantitative and qualitative nurses’ diary. The research was conducted with Afghan children aged 14-18 (n=254) and 20 nurse practitioners. Socio-demographic questionnaire and Short Form Health Survey (SF-36) were utilized as a quantitative data. Qualitative data collected by nursing diary to explain the quality of life of migrant children. Results: Socio-demographic data collected the study for 218 houses as 1.841 Afghans and study samples. SF-36 mean scores were 72.80±1.45 in the physical functioning, 71.80±1.27 social functioning, 78.46±2.36 in the physical problems, 82.28±2.13 in the emotional problems, 67.10±0.84 mental health, 56.34±0.97 in the energy and vitality, 70.62±1.39 in the bodily pain and 56.25±0.87 in the general perception of health. As a result of observing the selves and Afghans population, and reflecting on them by diaries, the nurse practitioners have raised plenty of concerns about their condition of life and faced with many cultural difficulties.Conclusion: This study has provided evidence Afghan migrants have a low quality of life which was affected by cultural and social resources.Keywords: Adolescent; afghan; migrant; nurse; quality of life.